Hydrocarbon gases of fluid inclusions in "Marmarosh diamonds" from veins in sediments in the flysch formation of the area of a new beskyd tunnel (Krosno zone of Ukrainian Carpathians) - Naumko, І.М.; Zankovych, G.О.; Kuzemko, Ya.D.; Dyakiv, V.О.; Sahno, B.Е. (Reports of the National Academy of Sciences of Ukraine, 2017)
Mainly methane and its homologues (probably, to C9) are identified in the composition of fluid inclusions in "Marmarosh diamonds" and calcite from carbonate-quartz veins and closed pores of rocks of the flysch formation of the Krosno zone of Folded Carpathians in the area of construction of a new branch of the Beskyd railway tunnel. The established high mass concentration of hydrocarbons points to a possibility of the transferring of mineral substances by the hydrocarbon-water fluid and the crystallization of parageneses with "Marmarosh diamonds" from such fluid. This evidences about the presence of the conjugated processes of migration of rising reduced hydrocarbon-containing fluids and formation of a veinlet-impregnated mineralization as a mineralohydrocarbongenesis significant indicator on one more area of spreading "Marmarosh diamonds" in sediments of the flysch formation of this structural-facial unit, which extends its oil- and gas-prospects.